The Aplication of the Team Games Tournament Learning Model Assisted by the Plickers Application to IPAS Learning Outcomes of Class IV Students of Labuang Baji II Kota Makassar - Sary, Firda Amanda; Achmad, Widya Karmila Sari; Pada, Amir (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2025)
The purpose of this research is to find out how to improve the IPAS learning results of students in class IV of SD Negeri Labuang Baji II Makassar City through the implementation of the Team Games Tournament (TGT) learning model with the help of the plickers application. The type of research used in this research is Class Action Research (PTK) with a qualitative approach. The research subjects are teachers and class IV students with 21 students, consisting of 9 men and 12 women as well as a teacher. This research data analysis technique is observation, test and documentation. The results of teacher activity observation in cycle I are included in the adequate category and the results of teacher activity observation in cycle II are included in the good category. The results of student activity observation in cycle I are included in the sufficient category and the results of student activity observation in cycle II are included in the good category. IPAS learning results of students in cycle I with an average score below KKTP and included in the incomplete category while IPAS learning results of students in cycle II with an average score above KKTP and included in the completed category. From the research results, it is known that the TGT model with the help of plickers application can improve the learning results of IPAS students in class IV of SD Negeri Labuang Baji II.